Digital Guidance and Counseling Transformation: Developing a Character Strength Website to Reduce Body Dysmorphic Disorder - Rochimah, Choerul; Vesti Dwi Cahyaningrum; M Iqbal Tawakkal (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to develop a website-based character strength counseling media to reduce symptoms of Body Dysmorphic Disorder (BDD) in vocational high school students. The main problem found in the field is the tendency of students, especially female adolescents majoring in Accounting and Visual Communication Design, who experience dissatisfaction with their physical appearance, such as compulsive mirror checking and social withdrawal. The results of quantitative data from 72 students showed 10% in the very low problem category, 44% low, 43% moderate, and 3% high. The guidance and counseling teacher at the school does not yet have special media to conduct tests or handle this phenomenon. The research method used is Research and Development (R&D) with the Borg and Gall model modified into 7 stages. The assessment instrument includes a validation questionnaire for material experts, media experts, and prospective users. The results of the validity test using inter-rater agreement analysis showed a score of 1.00 (very high classification) for the three assessment aspects. This website is designed using Google Sites by integrating the Cognitive Behavioral Therapy (CBT) approach, self-management techniques, and character strength content to help reduce the dominance of Body Dysmorphic Disorder thoughts by shifting focus (reframing), building a positive perspective, and self-validation or strengthening self-esteem. Thus, this media is declared very suitable for use by BK teachers as a tool in group counseling services to reduce BDD in vocational high school students. The results of the small group test resulted in a decrease in problem scores between the pretest and posttest, which means that there is an effect of using the character strength website media in reducing students' body dysmorphic. Thus, the development of this media is an effective solution to help students fulfill the developmental tasks of adolescence in accepting physical conditions adaptively.